THE EFFECT OF EMPLOYEE EMPOWERMENT, JOB ANALYSIS, AND CAREER DEVELOPMENT ON THE PERFORMANCE OF SECRETARIAT EMPLOYEES AT THE BATAM CITY GOVERNMENT OFFICE - Susana, Nova; Sumardin, Sumardin; Herman, Hendri (Yayasan Education and Social Center, 2026)
This study aims to analyse the influence of employee empowerment, job analysis, and career development on the performance of Secretariat employees at the Batam City Government Office, both partially and simultaneously. The approach is quantitative, using a survey method with questionnaires distributed to all 43 employees, resulting in saturated sampling. The data were analysed using multiple linear regression in SPSS. The results of the hypothesis testing indicate that employee empowerment has a significant effect on employee performance, as noted in a t-value of 3.918, which exceeds the t-table value of 1.685. The job analysis variable also has a substantial impact on employee performance, with a t-value of 4.459, which exceeds the t-table value of 1.685. Furthermore, career development has the most important influence on employee performance, with a t-value of 6.092, exceeding the t-table value of 1.685. Simultaneously, the three independent variables have a significant effect on employee performance, as evidenced by an F-value of 12.605, which exceeds the F-table value of 2.86. These findings confirm that optimising employee empowerment, clarity of job analysis, and systematic career development planning are essential factors in improving employee performance in the government environment.